Evidence of relative iron deficiency in platelet‐ and plasma‐pheresis donors correlates with donation frequency. Issue 6 (24th February 2016) - Li, Huihui; Condon, Frances; Kessler, Debra; Nandi, Vijay; Rebosa, Mark; Westerman, Mark; Shaz, Beth H.; Ginzburg, Yelena
Abstract : Background: The loss of iron stores and resulting iron deficiency is well documented in whole blood or red blood cell donors. We hypothesized that relative iron deficiency also occurs as a result of more frequent platelet‐ and plasma‐pheresis (apheresis) donation.Materials and Methods: To test this hypothesis, we proposed a pilot cross‐sectional study to analyze erythropoiesis‐ and iron‐related parameters in white male apheresis donors: (1) relative to controls, (2) in correlation with apheresis donation frequency, and (3) in correlation with pre‐donation platelet count.Results: Fifty eligible apheresis donors and eight controls were enrolled in the study. Apheresis donors were found to have a lower serum ferritin and serum hepcidin and exhibited evidence of iron restricted erythropoiesis relative to controls. Furthermore, among donors, lower MCV, CH r, hepcidin concentration, and serum ferritin were observed in more frequent apheresis donors. Correlations between donation frequency and hepcidin and ferritin were noted in apheresis donors.Conclusions: This pilot study demonstrates that apheresis donors are relatively iron deficient compared to controls and supports the premise that frequent apheresis donation correlates with relatively iron restricted erythropoiesis. An analysis of iron‐ and erythropoiesis‐related parameters in a broader population of frequent apheresis donors (i.e., female and non‐white donors) may demonstrate larger deficits and an even greater potential benefit of iron replacement. J. Clin. Apheresis 31:551–558, 2016. © 2015 Wiley Periodicals, Inc.